Advanced Urothelial Carcinoma: Overcoming Treatment Resistance through Novel Treatment Approaches - Bambury, Richard M.; Rosenberg, Jonathan E. (Frontiers in Pharmacology, 2013)
The current standard of care for metastatic urothelial carcinoma (UC) is cisplatin-based chemotherapy but treatment is generally not curative. Mechanisms of resistance to conventional cytotoxic regimens include tumor cell drug efflux pumps, intracellular anti-oxidants and enhanced anti-apoptotic signaling. Blockade of signaling pathways with small molecule tyrosine kinase inhibitors has produced dramatic responses in subsets of other cancers. Multiple potential signaling pathway targets are altered in UC. Blockade of the PI3K/Akt/mTOR pathway may prove efficacious because 21% have activating PI3K mutations and another 30% have PTEN inactivation (which leads to activation of this pathway). The fibroblast growth factor receptor 3 protein may be overactive in 50-60% and agents which block this pathway are under active development. Blockade of multiple other pathways including HER2 and aurora kinase also have potential efficacy. Anti-angiogenic and immunotherapy strategies are also under development in UC and are discussed in this review. Novel therapeutic approaches are needed in UC. We review the various strategies under development in this disease and discuss how best to evaluate and optimize their efficacy.